Modelling-based evaluation of the costs, benefits and cost-effectiveness of multipathogen point-of-care tests for sexually transmitted infections in symptomatic genitourinary medicine clinic attendees. Issue 9 (10th September 2018) - Huntington, Susie E; Burns, Richéal M; Harding-Esch, Emma; Harvey, Michael J; Hill-Tout, Rachel; Fuller, Sebastian S; Adams, Elisabeth J; Sadiq, S Tariq
Abstract : Objectives: To quantify the costs, benefits and cost-effectiveness of three multipathogen point-of-care (POC) testing strategies for detecting common sexually transmitted infections (STIs) compared with standard laboratory testing. Design: Modelling study. Setting: Genitourinary medicine (GUM) services in England. Population: A hypothetical cohort of 965 988 people, representing the annual number attending GUM services symptomatic of lower genitourinary tract infection. Interventions: The decision tree model considered costs and reimbursement to GUM services associated with diagnosing and managing STIs. Three strategies using hypothetical point-of-care tests (POCTs) were compared with standard care (SC) using laboratory-based testing. The strategies were: A) dual POCT for Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG); B) triplex POCT for CT-NG and Mycoplasma genitalium (MG); C) quadruplex POCT for CT-NG-MG and Trichomonas vaginalis (TV). Data came from published literature and unpublished estimates. Primary and secondary outcome measures: Primary outcomes were total costs and benefits (quality-adjusted life years (QALYs)) for each strategy (2016 GB, £) and associated incremental cost-effectiveness ratios (ICERs) between each of the POC strategies and SC. Secondary outcomes were inappropriate treatment of STIs, onward STI transmission, pelvic inflammatory disease in women, time to cure and total attendances. Results: In the base-case analysis, POC strategy C, a quadruplex POCT, was the most cost-effective relative to the other strategies, with an ICER of £36 585 per QALY gained compared with SC when using microcosting, and cost-savings of £26 451 382 when using tariff costing. POC strategy C also generated the most benefits, with 240 467 fewer clinic attendances, 808 fewer onward STI transmissions and 235 135 averted inappropriate treatments compared with SC. Conclusions: Many benefits can be achieved by using multipathogen POCTs to improve STI diagnosis and management. Further evidence is needed on the underlying prevalence of STIs and SC delivery in the UK to reduce uncertainty in economic analyses.